Social value of the built environment - Flora Samuel; Kelly Watson (Buildings & Cities, 2023)
Highlights The concept of social value has gained significant prominence in recent years in some countries, yet remains misunderstood. There is a recognised need for it to be better defined, interpreted and embedded in planning, design and operation. This will entail measurement and assessment. Social value is increasingly being considered alongside issues of quality of life and wellbeing, to both the individual and the community, but it remains challenging to reconcile social value in a meaningful way with the present value management approaches that dominate the construction and real estate industries. This special issue brings together a series of contributions to current thinking and critical discussion on social value, including empirical research from across the UK, Europe and Australia. It points to both new practices for the planning, design, construction and operation of projects. It identifies a series of gaps in the research, most notably a discussion of social value in the context of real estate, valuation and ‘environmental, social and corporate governance’ (ESG).